Expression of OsTPX Gene Improves Cellular Redox Homeostasis and Photosynthesis Efficiency in Synechococcus elongatus PCC 7942 - Kim, Young-Saeng; Kim, Jin-Ju; Park, Seong-Im; Diamond, Spencer; Boyd, Joseph S.; Taton, Arnaud; Kim, Il-Sup; Golden, James W.; Yoon, Ho-Sung (Frontiers in Plant Science, 2018)
Cyanobacterial 2-Cys peroxiredoxin (thioredoxin peroxidase, TPX) comprises a family of thiol antioxidant enzymes critically involved in cell survival under oxidative stress. In our previous study, a putative TPX was identified using a proteomics analysis of rice (Oryza sativa L. japonica, OsTPX) seedlings exposed to oxidative stress. This OsTPX gene is structurally similar to the Synechococcus elongatus TPX gene in the highly conserved redox-active disulfide bridge (Cys114, Cys236) and other highly conserved regions. In the present study, the OsTPX gene was cloned into rice plants and S. elongatus PCC 7942 strain to study hydrogen peroxide (H2O2) stress responses. The OsTPX gene expression was confirmed using semi-quantitative RT-PCR and western blot analysis. The OsTPX gene expression increased growth under oxidative stress by decreasing reactive oxygen species and malondialdehyde level. Additionally, the OsTPX gene expression in S. elongatus PCC 7942 (OT) strain exhibited a reduced loss of chlorophyll and enhanced photosynthesis efficiency under H2O2 stress, thereby increasing biomass yields twofold compared with that of the control wild type (WT) strain. Furthermore, redox balance, ion homeostasis, molecular chaperone, and photosynthetic systems showed upregulation of some genes in the OT strain than in the WT strain by RNA-Seq analysis. Thus, OsTPX gene expression enhances oxidative stress tolerance by increasing cell defense regulatory networks through the cellular redox homeostasis in the rice plants and S. elongatus PCC 7942.